Response of Drought Tolerant and Conventional Corn to Limited Irrigation - I. Kisekka; F. Lamm (Kansas Agricultural Experiment Station Research Reports, 2016)
The purpose of this study was to evaluate the response of two commercial hybrids (DKC 62-27 DGVT2PRO [drought tolerant trait (DT)] and DKC 62-98 VT2PRO [conventional]) to limited irrigation. Preliminary results from the 2014 and 2015 growing seasons at Southwest Research-Extension Center near Garden City, Kansas, indicate the effect of irrigation capacity on corn yield was significant (P<0.001)for both hybrids. The effect of the drought tolerance trait on yield was not significant (P>0.05)in both years. The effect of the interaction between irrigation capacity and corn hybrid on yield was also not significant (P>0.05). Hybrid type had a significant effect on crop water use (P<0.05). Crop water use ranged between 25.1 to 15.2 and 26.0 to 15.1 inches for the conventional and DT corn hybrids respectively. Averaged across treatments, the DT hybrid used approximately 3% more water compared to the locally adapted hybrid. It is worth noting that since the two hybrids were not isolines, any differences in crop water use could be attributed to differences in genetics and not the drought tolerant trait. The effects of the drought tolerant trait on water productivity were not significant in both years (P>0.05). Water productivity ranged between 10.9 to 3.6 and 11.2 to 5.6 bu/a/in for conventional and DT corn hybrids, respectively. As expected, DT and conventional corn hybrids had curvilinear yield response to irrigation and linear response to seasonal crop water use/evapotranspiration (ETc). The marginal water productivity for conventional and DT hybrids ranged from 18.4 to 14.5 bu/a/in and from 15.2 to 14.6 bu/a/in respectively. These preliminary results indicate no significant differences in yields and water productivity between DT and conventional hybrids under full and limited irrigation. More research is needed to confirm these findings.
Keywords: corn; drought tolerant corn; limited irrigation; crop water use; water productivity response; irrigation management